Pathology of the Thyroid Gland in Women Rheumatoid Arthritis - Shodikulova Gulandom Zikiryayevna; Shonazarova Nodira Xudoyberdiyevna; Sheranov Atxam Mamadiyarovich (Zien Journals, 2022)
Endocrine disorders are of primary importance in the occurrence and progression of rheumatic diseases. Often, endocrine restructuring that occurs during puberty, menopause, pregnancy, childbirth, and abortion serves as a background for the development of connective tissue diseases. At the same time, the change in neuroendocrine status is an integral component of the progression of rheumatic diseases. Especially distinct hormonal shifts were found on the part of the thyroid gland in rheumatoid arthritis (RA). The prevalence of thyroid pathology in general among patients with rheumatoid arthritis, according to literature data, reaches 34%, and Hashimoto's thyroiditis, according to various authors, from 4 to 13.5%. In addition, the greatest susceptibility to RA in women of reproductive age indicates a certain role of sex hormones in the pathogenesis of the disease. Metabolic and degenerative changes in connective tissue largely determine the pathogenesis and clinical picture of various diseases. Rheumatic diseases, the most common of which is rheumatoid arthritis (RA), make up a significant proportion of the pathology of the joints, musculoskeletal system, and connective tissue. It affects 0.5—1% of the world's population, which is about 63 million patients.
Keywords: rheumatoid arthritis; autoimmune thyroiditis; hypothyroidism